The evolution of parents' beliefs about childhood cancer during diagnostic communication: a qualitative study in Guatemala. Issue 5 (26th May 2021) - Graetz, Dylan; Rivas, Silvia; Fuentes, Lucia; Cáceres-Serrano, Ana; Ferrara, Gia; Antillon-Klussmann, Federico; Metzger, Monika; Rodriguez-Galindo, Carlos; Mack, Jennifer W
Abstract : Introduction: Fatalistic cancer beliefs may contribute to delayed diagnosis and poor outcomes, including treatment abandonment, for children with cancer. This study explored Guatemalan parents' cancer beliefs during initial paediatric cancer communication, and the sociocultural and contextual factors that influence these beliefs. Methods: Twenty families of children with cancer were included in this study. We audio-recorded psychosocial conversations with psychologists and diagnostic conversations with oncologists, then conducted semi-structured interviews with parents to explore the evolution of their cancer beliefs. Audio-recordings were transcribed and translated from Spanish into English, with additional review in both languages by bilingual team members. All 60 transcripts were thematically analysed using a priori and novel codes. Results: Guatemalan parents' beliefs evolve as they learn about cancer through various sources. Sources of information external to the cancer centre, including prior experiences with cancer, media exposure, community discussion and clinical encounters, contribute to pre-existing beliefs. Many parents' pre-existing cancer beliefs are fatalistic; some are influenced by Mayan spirituality. Sources internal to the cancer centre include psychologists and oncologists, other providers, other patients and families. Psychologists acknowledge pre-existing beliefs and deliver cancer education using verbal explanations and hand-drawings. Oncologists provide diagnostic information and outline treatment plans. Both support hope by providing a path toward cure. Parents' lived experience is a culmination of sources and simultaneously independent. Ultimately most parents arrive at an understanding of cancer that is consistent with an allopathic medical model and offers optimism about outcomes. Conclusion: An interdisciplinary communication process that includes cancer education, is attentive to pre-existing beliefs, and supports hope may encourage acceptance of the allopathic medical model and need for treatment. Providers in settings of all resource levels may be able to use these techniques to support cross-cultural cancer communication, reduce treatment abandonment and improve therapy adherence.